Strengthening maternal referral systems during public health emergencies: insights from Indonesia’s covid-19 response - Laksana, Muhammad Ardian Cahya; Damayanti, Nyoman Anita; Habibie, Pandu Hanindito; Suhargono, Mochammad Hud; Dewi, Erni Rosita; Santoso, Budi; Sukarjiyah, Waritsyah; Izza, Alifina; Zakiya, Nurani Zulfa (Jurnal Ners, 2025)
Introduction: This study assesses hospital readiness in maternal referral hospitals six months after the onset of the pandemic, aiming to inform future public health emergency responses. Methods: A descriptive and exploratory mixed-methods design was employed. Surveys and focus group discussions were conducted with 127 hospitals in the COVID-19 maternal referral hospitals by the East Java Provincial Government using the modified WHO hospital readiness checklist for COVID-19 2020. Quantitative data were analyzed descriptively, and qualitative data from focus group discussions were thematically analyzed to get deeper insights into the challenges faced by hospitals. Results: A total of 105 hospitals (83%) responded to the survey. While PPE supplies were largely adequate, gaps in infrastructure, including negative-pressure rooms, isolation areas, and diagnostic capacity, persisted. Financial constraints, particularly delays in the National Health Insurance Scheme (BPJS Kesehatan) claims, further strained hospital operations. FGDs revealed that PCR delays, staffing shortages, and underdeveloped referral coordination systems hindered the delivery of maternal services. Conclusions: Strengthening maternal referral systems requires improving diagnostic capabilities, investing in essential infrastructure, and ensuring timely financial reimbursement. Collaborative efforts among the Ministry of Health, BPJS Kesehatan, and healthcare facilities are crucial to enhancing maternal healthcare resilience during future public health emergencies.